2022
DOI: 10.1111/tbed.14724
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and molecular characterization of the avian infectious bronchitis virus GI‐23 in commercial broiler farms from South America

Abstract: Avian infectious bronchitis virus (IBV) is the etiological agent of a highly contagious disease in the poultry industry. The spike protein (S1 subunit) is responsible for the molecular diversity of the virus and many genetic types, and lineages are described worldwide. IBV genetic type I—strain 23 (GI‐23) has spread across different continents (including Asia, Europe and Africa), causing multiple outbreaks and severe economic losses throughout the poultry industry in the last decade. The present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Unclassified variants in the GI-1 and GI-11 lineages were sequenced and the phylogenetic analysis ( Figure 1 ) showed new viral strains, classified as GI-23. This result is in agreement with earlier research reported by Ikuta et al (2022) [ 26 ]. Although, in general, the amino acid sequences obtained in the present study were very similar to the sequences presented by Ikuta et al (2022) [ 35 ] ( Table 1 of such work), through the analyses carried out in the present study, some differences were found.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Unclassified variants in the GI-1 and GI-11 lineages were sequenced and the phylogenetic analysis ( Figure 1 ) showed new viral strains, classified as GI-23. This result is in agreement with earlier research reported by Ikuta et al (2022) [ 26 ]. Although, in general, the amino acid sequences obtained in the present study were very similar to the sequences presented by Ikuta et al (2022) [ 35 ] ( Table 1 of such work), through the analyses carried out in the present study, some differences were found.…”
Section: Discussionsupporting
confidence: 94%
“…Among the group assigned as “not classified”, nine isolates were subjected to S1 glycoprotein gene sequencing. In the phylogenetic analysis, we used a sequence dataset of the strains frequently found in Brazil and GI-23 [ 26 ]. According to the phylogenic relationship shown in Figure 1 , all nine isolates were grouped within the GI-23 strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, GI-17 (DMV/1639-like strains) is the major variant of IBV circulating in US commercial poultry; it was initially isolated in 2011 and began causing significant diseases in 2014/2015 [ 17 ]. In Latin America, lineages GI-1, GI-11, GI-16, and GI-23 are coexisting at present in Brazil, and the prevalent genotypes are GI-13 (793B-type) and GI-16 (Q1) in Chile [ 28 , 29 , 37 ]. In Africa, such as Egypt, Morocco, and Nigeria, the co-epidemic lineages include GI-1 (Mass-type) and GI-13 (793B-type); in addition to this, there are Egyptian IBV variants 1, 2 (GI-23) in Egypt, Moroccan isolates (GI-21) in Morocco, and QX-type (GI-19) strains in Nigeria [ 20 , 49 , 50 , 51 ].…”
Section: Worldwide Distribution Of Avian Infectious Bronchitis Virusmentioning
confidence: 99%